2023
DOI: 10.1093/eurheartj/ehad346
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pulmonary artery pressure monitoring in patients with chronic heart failure: a meta-analysis of three randomized controlled trials

Abstract: Background and Aims Adjustment of treatment based on remote monitoring of pulmonary artery (PA) pressure may reduce the risk of hospital admission for heart failure (HF). We have conducted a meta-analysis of large randomized trials investigating this question. Methods A systematic literature search was performed for randomized clinical trials (RCTs) with PA pressure monitoring devices in patients with HF. The primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…25 Across all 3 trials, there was also a higher number of cumulative medication changes in the pulmonary artery pressure monitoring group, especially for diuretics. 25 Pulmonary artery pressure monitoring is an invasive procedure, which may limit acceptability and scalability. However, remote monitoring and clear objective markers of clinical improvement or deterioration may trigger interactions between clinicians and patients to optimize medical therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…25 Across all 3 trials, there was also a higher number of cumulative medication changes in the pulmonary artery pressure monitoring group, especially for diuretics. 25 Pulmonary artery pressure monitoring is an invasive procedure, which may limit acceptability and scalability. However, remote monitoring and clear objective markers of clinical improvement or deterioration may trigger interactions between clinicians and patients to optimize medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…25 A meta-analysis of 3 randomized clinical trials (MONITOR-HF, CHAM-PION, and GUIDE-HF) demonstrated that among patients with remote pulmonary artery pressure monitoring, total HF hospitalizations were reduced by 30%, independent of EF. 25 Across all 3 trials, there was also a higher number of cumulative medication changes in the pulmonary artery pressure monitoring group, especially for diuretics. 25 Pulmonary artery pressure monitoring is an invasive procedure, which may limit acceptability and scalability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A meta‐analysis of the three CardioMems trials—CHAMPION, GUIDE‐HF, and MONITOR‐HF—reported the use of CardioMEMS to result in a significant reduction in HF hospitalisations, with a hazard ratio of 0.70 (95% confidence interval 0.58–0.86) 4 . This pooled effect shows the potential for CardioMEMS across multiple countries with significantly different healthcare systems and against evolving background therapy.…”
mentioning
confidence: 92%